М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
akm0910
akm0910
09.04.2023 06:58 •  Алгебра

Решите неравенство x^2 - 10*x + 21 > 0

👇
Ответ:
Aliska504
Aliska504
09.04.2023
X^2-10x+21>0
По теореме Виета
x1*x2=21
x1+x2=10
=> x1=3, x2=7
ответ: x∈(-∞;3)∪(7;+∞)
4,6(94 оценок)
Открыть все ответы
Ответ:
малина106
малина106
09.04.2023

Объяснение:

ОДЗ : cos2x ; sin2x

cosx ± 1/4 ; sinx ; cosx 0

x ± arccos0,25 + 2πk ; x πk/2 , k ∈ z

2*2cos^2 x - 2 = 1/2cos2x * ( ... )

2cos2x = 1/2cos2x * ( ... )

можно поделить на cos2x, так как cos2x также есть в знаменателе, то есть корни мы не теряем

2 = 1/2 * ( ... )

для удобства делаем замену: пусть 2x = t

2 = 1/2 * (/cost + 1/sint)

2 = /2cost + 1/2sint

(sint + cost) / 2costsint = 2

-2 (-/2 sint - 1/2 cost) / 2costsint = 2

-2 (-sin (π/3) sint - cos(π/3) cost) / 2costsint = 2

выносим минус за скобки и сокращаем 2

а также, используя формула приведения косинуса, только в обратную сторону, делаем все красиво

cos (π/3 - t) / costsint = 2

cos (π/3 - t) = 2costsint

cos (π/3 - t) - sin2t = 0

sin (π/2 - (π/3 - t) - sin2t = 0

sin (π/6 + t) - sin2t = 0

используем sin(t) - sin(s) = 2cos((t + s)/2) * sin ((t - s)/2)

и делим на 2

cos ((π + 18t)/12) * sin((π - 6t)/12) = 0

cos ((π + 18t)/12) = 0

sin ((π - 6t)/12) = 0

t = 5π/18 + 2πk/3

t = π/6 + 2πk

вспоминаем, что t = 2x

x = 5π/36 + πk/3

x = π/12 + πk

k ∈ Z

4,7(70 оценок)
Ответ:
йцукен56
йцукен56
09.04.2023
First, we'll try to plug in the value:
#lim_{x to -oo}x+sqrt(x^2+2x) = -oo + sqrt(oo-oo)#
We're already encountering a problem: it is simply not allowed to have #oo-oo#, it's like dividing by zero.
We need to try a different approach.
Whenever I see this kind of limit, I try to use a trick:
#lim_{x to -oo}x+sqrt(x^2+2x)#
#= lim_{x to -oo}x+sqrt(x^2+2x)*(x-sqrt(x^2+2x))/(x-sqrt(x^2+2x))#
These are the same becaus the factor we're multiplying with is essentially #1#.
Why are we doing this? Because there exists a formula which says: #(a-b)(a+b) = a^2-b^2#
In this case #a = x# and #b = sqrt(x^2+2x)#
Let's apply this formula:
#lim_{x to -oo}(x^2-(sqrt(x^2+2x))^2)/(x-sqrt(x^2+2x))#
#= lim_{x to -oo}(x^2-x^2-2x)/(x-sqrt(x^2+2x))#
#= lim_{x to -oo}(-2x)/(x-sqrt(x^2+2x))#
Now we're going to use another trick. We'r going to use this one, because we want to get the #x^2# out of the square root:
#lim_{x to -oo}(-2x)/(x-sqrt(x^2(1+2/x))#
If you look carefully, you see it's the same thing.
Now, you might say that #sqrt(x^2) = x#, but you have to remember that #x# is a negative number. Because we're taking the positive square root, #sqrt(x^2) = -x# in this case.
#= lim_{x to -oo}(-2x)/(x+xsqrt(1+2/x))#
#= lim_{x to -oo}(-2x)/(x(1+sqrt(1+2/x)))#
We can cancel the #x#:
#= lim_{x to -oo}(-2)/(1+sqrt(1+2/x))#
And now, we can finally plug in the value:
#= -2/(1+sqrt(1+2/-oo))#
A number divided by infinity, is always #0#:
#= -2/(1+sqrt(1+0)) = -2/(1+1) = -2/2 = -1#
This is the final answer.
Hope it helps.
4,7(80 оценок)
Это интересно:
Новые ответы от MOGZ: Алгебра
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ